Osteoprotegerin and Osteopontin Serum Levels are Associated with Vascular Function and Inflammation in Coronary Artery Disease Patients - Maniatis, Konstantinos; Siasos, Gerasimos; Oikonomou, Evangelos; Vavuranakis, Manolis; Zaromytidou, Marina; Mourouzis, Konstantinos; Paraskevopoulos, Thodoros; Charalambous, Georgios; Papavassiliou, Athanasios G.; Tousoulis, Dimitris (Current Vascular Pharmacology, 2020)
Background: Osteoprotegerin and osteopontin have recently emerged as key factors in both vascular remodelling and atherosclerosis progression. Interleukin-6 (IL-6) is an inflammatory cytokine with a key role in atherosclerosis. The relationship of osteoprotegerin, osteopontin, and IL-6 serum levels with endothelial function and arterial stiffness was evaluated in patients with coronary artery disease (CAD). Methods: We enrolled 219 patients with stable CAD and 112 control subjects. Osteoprotegerin, osteopontin and IL-6 serum levels were measured using an ELISA assay. Endothelial function was evaluated by flow-mediated dilation (FMD) in the brachial artery and carotid-femoral pulse wave velocity (PWV) was measured as an index of aortic stiffness. Results: There was no significant difference between control subjects and CAD patients according to age and sex. Compared with control subjects, CAD patients had significantly impaired FMD (p<0.001) and increased PWV (p=0.009). CAD patients also had significantly higher levels of osteoprotegerin (p<0.001), osteopontin (p<0.001) and IL-6 (p=0.03), compared with control subjects. Moreover, IL-6 levels were correlated with osteoprotegerin (r=0.17, p=0.01) and osteopontin (r=0.30, p<0.001) levels. FMD was correlated with osteoprotegerin levels independent of possible confounders [b coefficient= - 0.79, 95% CI (-1.54, -0.05), p=0.04]. Conclusion: CAD patients have increased osteoprotegerin, osteopontin and IL-6 levels. Moreover, there is a consistent association between osteoprotegerin and osteopontin serum levels, vascular function and inflammation in CAD patients. These findings suggest another possible mechanism linking osteoprotegerin and osteopontin serum levels with CAD progression through arterial wall stiffening and inflammation.
Keywords: arterial stiffness